Awareness of the Green Dentistry Concept among Dental Professionals in Tertiary Care Dental Hospital, Rawalpindi - Vasiqa Bano; Erum Amin; Samar Maqbool; Syed Ali Hassan; Abeer Baber; Raabia Urooj (Life and Science, 2024)
Objective: To assess awareness of green dentistry among graduates, postgraduates and general dentists Study Design: Descriptive Cross-sectional. Place and Duration of Study: The study was conducted at Armed Forces Institute of Dentistry (AFID) Rawalpindi, Pakistan from August 2022 to October 2022. Methods: Based on a pre-validated survey questionnaire comprising of 20 close-ended questions assessing the awareness regarding green dentistry. Male and female respondents consisting of General dentists, graduates, postgraduate and house officers, and practitioners of AFID who gave consent were included in the study. The sample size was calculated using the WHO calculator and 332 respondents were recruited and the questionnaire was distributed, responses were then analyzed using SPSS version 22 and the p-value < 0.05 was considered significant. Results: Out of the 332 participants 148 were post-graduates, 109 were Graduates, 35 were consultants and 40 were general dentists with the age range of 25 to 50 years. 248 participants were females and 84 were males and 100% response rate was observed. Postgraduates (47%) were more aware of the eco-friendly dentistry concept the difference was found statistically significant (p-value <0.000). Conclusion: Most of the respondents were aware of the green dentistry concept, those who had little knowledge were accepting the concept and were enthusiastic to inculcate these practices in their practices.